Synthesis and Characterization of Oxomolybdenum(V) and Dioxomolybdenum(VI)Complexes of 2,3-Dimethyl-1-phenyl 4-(2-Hydroxy-5-bromobenzylideneamino)-pyrazol-5-one - Harikumaran Nair, M.L.; Pramila Gladis, M.S. (Asian Journal of Chemistry, 2010)
A few oxomolybdenum(V) and dioxomolybdenum(VI) complexes of the ligand 2,3-dimethyl-1-phenyl-4-(2-hydroxy- 5-bromobenzylideneamino)pyrazol-5-one (BSAP) with the composition [MoO(BSAP)XCl2] and [MoO2(BSAP)XCl] (where X = Cl, NCS, NO3, ClO4) have been prepared. The complexes were characterized by elemental analysis, molar conductance, magnetic susceptibility measurements and IR, UV, 1H NMR and ESR spectroscopic studies. The thermal behaviour of some of the complexes were also examined. The ligand and some of the complexes were screened for their possible antibacterial activities against gram positive and gram negative bacteria. All the oxomolybdenum(V) complexes showed normal magnetic behaviour. The molar conductance values of the complexes indicate that they are non-electrolytes. The X-ray diffraction patterns of the complex [MoO(BSAP)Cl3] have been examined and was indexed. The results show that the complex belongs to the orthorhombic crystal system with unit cell dimensions a = 13.6167 Å, b = 10.3163 Å and c = 7.8616 Å. The ligand behaves as a neutral bidentate one. The complexes are found to be monomeric and neutral with distorted octahedral geometry.